The international wine trade: Recent trends and critical issues - Angela Carla Mariani; Eugenio Pomarici; Vasco Ladislao Boatto (Wine Economics and Policy, 2012)
This paper aims to contribute to the understanding of international wine trade complexities, focusing on the period 2000-2011. Since 2000 the wine trade has grown significantly and its structure has experienced major changes. Such changes are shaping the current competitive scenario of the wine market and are the base elements for its future development. The paper analyses the growth of world wine imports, considering all wines together and the single categories recognized by global statistics (bottled, bulk and sparkling wine). It then describes the changes in the geography of importers with the emergence of new markets and the competitive performance of the main suppliers. The bulk wine trade, the re-export of wine and the exposure of trade flows to trade barriers are also analyzed in detail. Finally, on the basis of the dominant trend in wine consumption and changes in the supply chain, the critical issues arising from analysis are examined, with the need for further research being underlined.
Keywords: 330; Competitive performance; International trade; Wine